0203 Farming and mortality from leukaemia in taiwan. (21st August 2017) - Chang, Chih-Ching; Ho, Shu-Chen; Yang, Chun-Yuh
Abstract : Agricultural workers might be at an increased risk for several cancers, including leukaemia, in mortality and incidence studies. A death certificate-based case-control study was designed to investigate whether farmers in Taiwan had an increased risk of dying from leukaemia (ICD-9 codes 204–208). All deaths of Taiwan residents were retrieved from the Taiwan Death Certification Registry. Cases were defined as deaths from leukaemia who were at least 50 years of age between 1997 and 2009. Controls were deaths from all causes other than cancers. We extracted information on sex, marital status, year of birth, year of death, cause of death, county of residence, and usual occupation from each death certificate. Logistic regression models were applied to calculate the mortality odds ratio (MOR) and their 95% confidence interval (CI). A total of 32 456 deceased farmers were identified between 1997 and 2009. Of these 32 456 decedents, 140 deaths were coded as leukaemia. After adjusted for gender, marital status, age at death, year of death, and urbanisation level, farmers were not with significant increase in the risk of leukaemia (aMOR=0.92, 95% CI=0.77–1.10), compared to non-farmers. There were no significant difference in term of the death by age and gender between farmers and non-framers. The patterns of death by age and gender were similar between farmers and non-farmers. Further investigation of leukaemia risk among farmers is warranted.